响应面优化氯化胆碱-丙三醇体系提取芝麻蛋白工艺条件 "Response surface optimization of the extraction process conditions for sesame protein using choline chloride-glycerol system" - 曹培换1，张晨霞1，刘燕2，马宇翔1，刘华敏1，郑永战1，3 "CAO Peihuan1，ZHANG Chenxia1，LIU Yan2，MA Yuxiang1， LIU Huamin1，ZHENG Yongzhan1,3" (Zhongguo youzhi)
为提高芝麻油副产物芝麻饼粕中蛋白质的综合利用率，以芝麻粕为原料，选用氯化胆碱-丙三醇（物质的量比1∶ 3）体系（低共熔溶剂，DES）提取芝麻蛋白，通过单因素试验和响应面试验优化提取工艺条件，分析最优条件下提取的芝麻蛋白的功能特性，并采用傅里叶变换红外光谱和扫描电子显微镜对芝麻蛋白进行结构表征，同时与传统碱溶酸沉法提取工艺进行对比。结果表明：DES提取芝麻蛋白的最优条件为DES含水量10%、固液比1∶ 29.4、提取温度59.0 ℃、提取时间1 h、搅拌速度 750 r/min，在此条件下芝麻蛋白提取率为（64.65±0.52）%，显著低于碱溶酸沉法芝麻蛋白的提取率〔(74.19±1.79)%〕；DES提取的芝麻蛋白的溶解性、吸油性、泡沫稳定性和乳化稳定性均显著高于碱溶酸沉法提取的，而吸水性显著低于碱溶酸沉法提取的；DES提取的芝麻蛋白的β-折叠含量显著低于碱溶酸沉法提取的，而其他二级结构（α-螺旋、无规卷曲、β-转角、β-逆折叠）的含量则显著高于碱溶酸沉法提取的。综上，DES提取法可作为新型绿色的芝麻蛋白提取方法。 To improve the comprehensive utilization rate of protein in sesame cake and meal, a by-product of sesame oil, sesame protein was extracted from sesame meal using choline chloride -glycerol (molar ratio 1∶ 3) system (deep eutectic solvent, DES), the extraction process conditions were optimized through single factor experiments and response surface methodology, and the functional characteristics of sesame protein extracted under the optimal conditions were analyzed. Fourier transform infrared spectroscopy and scanning electron microscopy were used to characterize the structure of sesame protein. In addition, the sesame protein extracted by DES method was compared with that by alkali solution-acid precipitation method. The results showed that the optimal conditions for extracting sesame protein were as follows: moisture content in DES 10%, solid-liquid mass ratio 1∶ 29.4, extraction temperature 59.0 ℃, extraction time 1 h, and stirring speed 750 r/min. Under these conditions, the extraction rate of sesame protein was (64.65 ±0.52)%, significantly lower than that of the alkali solution-acid precipitation method((74.19±1.79)%). The solubility, oil absorption, foam stability and emulsification stability of sesame protein extracted by DES were significantly higher than those extracted by alkali solution-acid precipitation method, while the water absorption was significantly lower than that extracted by alkali solution-acid precipitation method. The β- folding contents of the protein obtained by DES was significantly lower than that obtained by alkali solution-acid precipitation method, while the contents of other secondary structures (α-helix, aperiodical coil, β-turn angle, β-inverse folding) were significantly higher than those obtained by alkali solution-acid precipitation method. In conclusion, the DES extraction method can be used as a new green sesame protein extraction method.